PATRONAGE DALAM DENDANG MINANG BASIROMPAK VERSUS BAUWOIK - Maspon Herizal (Paraguna, 2015)
The purpose  of this research  is to determine the function  of patronage in Basirompak and Bauwoik cases  in Payakumbuh.  This research applies descriptive-analytical approach undertaken by  a systematic procedure. The the theory applied is the decisional  theory that  explains about   thinking concept of culture,  music, patronage, and social events.  Basirompakand Bauwoik  are  originatedfrom  Payakumbh.The developmentofIslamin thelocal community  is not  necessarily  removing  the animistic understanding.  This ideology persists in the development of Basirompak and Bawoik inwhich  ever show always creates  the scary impression especially among    women.    Such  condition affects   the psychological community    that   the  existence   of  Basirompakand  Bauwoik   become detestable  andeventually marginalized from public support. However,  the patronage makes Basirompak  still be  maintained.  This is  not  valid  on Bauwoik which gradually  becomes drowned and died